Severe cytomegalovirus infection and immunosuppressive therapy in pediatric liver transplantation - (:unkn) unknown (My University, 1990)
Twenty-two post-orthotropic liver transplant (OLT) recipients were studied to investigate the clinical, laboratory and histopathological differences between rejection and CMV infection. The mean age at the time of transplantation was five years. Nine of 22 (41%) patients developed positive CMV, CF-IgG and IgM antibody titers and cultures for CMV following surgery, and three (group 1a) developed interstitial pneumonitis. CMV specific inclusion bodies were found in lung and liver biopsies. Two patients in group 1a were treated successfully with DHPG and decreasing immunosuppressive treatment, while the third died. Clinical presentation of rejection episodes were similar in all groups. CMV infected patients (group 1) received more transfusions of blood and blood products than the non-infected patients (group 2). Rejection episodes occurred sooner and more frequently in group 1a than in group 1b (CMV infected-asymptomatic) and group 2 (non-infected). Group 2 received fewer steroid boluses as well as azathioprine and OKT 3. A percutaneous liver biopsy with routine stains helped detect CMV when inclusion bodies were seen. We conclude that culture proven CMV infection is common post-OLT. Severe CMV infection occurred more frequently in those who had received greater doses of immunosuppressive therapy for possible graft rejection. Monitoring CMV infection following OLT is absolutely necessary. After OLT, decreasing the immunosuppressives and using antiviral agents are important in the management of CMV infection.
Keywords: Female; Humans; Immunosuppressive Agents; Adolescent; Infant; Male; Child; Retrospective Studies; Child, Preschool; Graft Rejection; Cytomegalovirus Infections; Cytomegalovirus; Liver Transplantation